Testicular morphological changes during the seasonal reproductive cycle in the bullfrog Rana catesbeiana - Cerri, Estela Sasso [UNESP]; De Faria, Flávio P.; Freymüller, Edna; Miraglia, Sandra M. (Wiley, 2004)
Spermatogenesis and steroidogenesis undergo seasonal variations during the reproductive cycle in amphibians. Testicular morphological and morphometric seasonal variations as well as interstitial lipidic inclusions and intralobular glycoconjugates were evaluated during seasonal cycle of Rana catesbeiana. Testes of frogs collected during the annual seasons were weighed for calculation of GSI (Gonadosomatic index). Seminiferous lobule diameters (DSL) and volume densities of seminiferous lobules (VvSL), excretory ducts (VvED), and interstitial tissue (VvIT) were analyzed. Semithin sections were submitted to Periodic Acid-Schiff (PAS) and Alcian Blue (AB) methods for detection of glycoconjugates, while lipidic inclusions were detected by Sudan Black B. GSI showed no significant variations during the year. Since VvED and VvIT increased significantly during summer and were inversely proportional to VvSL, a compensatory effect between the testicular compartments may be related to the maintenance of GSI. During autumn/winter, larger lobular diameters were observed in comparison to spring/summer when spermiogenesis and spermiation were commonly observed. The increased VvIT and the numerous lipidic inclusions in the interstitial cells during summer suggest a relationship between spermiogenesis and steroidogenesis. Besides the structural stability variations occurring in the IT and SL, a possible paracrine interaction between ED and IT should be also involved in the IT development during summer. The presence of PAS and AB-positive globular structures were observed in the seminiferous lobules and excretory ducts. These structures containing acid glycoconjugates appear to be Sertoli cell apical portions, which are accumulated in the lumen of the seminiferous lobules mainly during spermiation. © 2004 Wiley-Liss, Inc.
Keywords: alcian blue; azo compound; glycoconjugate; sudan black; analysis of variance; animal; comparative study; frog; histology; male; metabolism; morphometrics; periodic acid Schiff stain; physiology; reproduction; season; testis; Alcian Blue; Analysis of Variance; Animals; Azo Compounds; Body Weights and Measures; Glycoconjugates; Histological Techniques; Male; Periodic Acid-Schiff Reaction; Rana catesbeiana; Reproduction; Seasons; Testis; Amphibia; Anura